The Development of Nomadism in Ancient Northeast Africa - Sadr, Karim (Anniversary Collection., 2017)
Nomadism was one of the most important strategies for survival, and it is still the strategy of choice form many cultures in Africa and the Near East. Nomadism can be best understood through an examination of its origins, by asking why and how nomadism emerged as a way of life.